Tackling Spillovers by Taxing Corporate Income in the European Union at Source - Sijbren Cnossen (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper surveys and evaluates the corporation tax (CT) systems of the Member States of the European Union on the basis of a comprehensive taxonomy of actual and potential regimes, which have as their base either profits, profits and interest, or economic rents. The current regimes give rise to various instate and interstate spillovers, which violate the basic tenets – neutrality and subsidiarity – of the single market. The trade-offs between the implications of these tenets – harmonization and diversity, respectively – can be reconciled by a bottom-up, reversible strategy of strengthening source-based taxation and approximating tax rates. The strategy starts with dual income taxation, proceeds with final source withholding taxes and rate approximation, and is made complete by comprehensive business income taxation. Common base taxation, if desired, should probably be left to the Member States themselves.
Keywords: H25; H32; H71; H73; H77; 330; corporation tax; European Union; tax coordination; tax spillovers; dual income tax; comprehensive business income tax; allowance for corporate equity; rate of return allowance